Principal’s Managerial in Improving the Quality of Education in Primary School - Nuryani, Nuryani; Harapan, Edi; Wardiah, Dessy (Yayasan Sembilan Pemuda Indonesia, 2021)
This qualitative study explored the principal's managerial in improving the quality of education in primary school. This research was conducted at SDN 2 Tungkal Ilir, SDN 10 Tungkal Ilir and SDN 18 Tungkal Ilir. The research instruments in this study were interviews. Qualitative data analysis is iterative and continuous effort. Three stages of data analysis were carried out, data reduction, data presentation and conclusion drawing. The results of this study concluded that the principal was able to carry out managerial in improving the quality of education at the State Elementary School in Tungkal Ilir. The way the principal in fostering, directing teachers in the learning process is considered good through the principal's managerial. Besides that, the principal in carrying out managerial tasks has been able to overcome obstacles at school. This paper contribute to more deeply concern on principal’s managerial where we could have good quality of education.